Indoor Air Quality Assessment in Selected Warsaw Flats: Quantitative and Qualitative Analysis of Airborne Fungi - Augustyniuk-Kram, Anna; Żyro, Kacper; Ilieva-Makulec, Krassimira (Studia Ecologiae et Bioethicae, 2025)
This study investigates the sanitary condition of indoor air in thirty flats across thirteen districts of Warsaw, Poland, by analysing the concentration and diversity of airborne microscopic fungi. A total of 270 air samples were collected from bathrooms, kitchens, and bedrooms using the MAS-100 Eco® impact sampler and cultured on YGC medium. Fungal colony forming units (CFU m-³) were quantified and identified to the genus level. The results revealed that fungal contamination exceeded acceptable thresholds in 70% of bathrooms and kitchens, and in 97% of bedrooms, with concentrations ranging from 1.0 x 102 to over 2.5 x 103 CFU m-³ of the air. Thirteen fungal genera were identified, with Cladosporium (100% of flats), Penicillium (90%), and Alternaria (60%), Aureobasidium (57%), and yeast-like fungi (53%) being the most prevalent. Statistical analysis showed significant correlations between fungal abundance and flat characteristics and residents’ habits, including location, year of construction, building material, floor area, presence of pets, smoking habits, cleaning frequency, number of windows, ventilation frequency, and bathroom fixtures. The findings highlight the importance of regular monitoring of indoor fungal presence to mitigate health risks and improve living conditions.